2016
DOI: 10.5194/gmd-9-841-2016
|View full text |Cite
|
Sign up to set email alerts
|

Towards a representation of priming on soil carbon decomposition in the global land biosphere model ORCHIDEE (version 1.9.5.2)

Abstract: Abstract. Priming of soil carbon decomposition encompasses different processes through which the decomposition of native (already present) soil organic matter is amplified through the addition of new organic matter, with new inputs typically being more labile than the native soil organic matter. Evidence for priming comes from laboratory and field experiments, but to date there is no estimate of its impact at global scale and under the current anthropogenic perturbation of the carbon cycle. Current soil carbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 62 publications
1
62
0
Order By: Relevance
“…Contrary to what was shown by Cardinael et al (2015c) in long-term bare fallows receiving contrasted organic amendments, the addition of another SOC pool could not surpass the inclusion of the priming effect in terms of model performance. Together with Wutzler and Reichstein (2013) and Guenet et al (2016), this study therefore suggests that implementing the priming effect into SOC models would improve model performances, especially when modeling deep SOC profiles.…”
Section: Vertical Representation Of Soc Profiles In Modelsmentioning
confidence: 99%
“…Contrary to what was shown by Cardinael et al (2015c) in long-term bare fallows receiving contrasted organic amendments, the addition of another SOC pool could not surpass the inclusion of the priming effect in terms of model performance. Together with Wutzler and Reichstein (2013) and Guenet et al (2016), this study therefore suggests that implementing the priming effect into SOC models would improve model performances, especially when modeling deep SOC profiles.…”
Section: Vertical Representation Of Soc Profiles In Modelsmentioning
confidence: 99%
“…Priming parameter for mineralization slow 194.03 (Guenet et al, 2016) priming_param ( Value within the range found in literature for fast pool of DOC (Boddy et al, 2008;Kalbitz et al, 2003;Qualls and Haines, 1992;Turgeon, 2008) Geosci. Model Dev.…”
Section: Competing Interestsmentioning
confidence: 99%
“…The not-respired, recycled DOC (DOC Recycled ) coming from active, slow and passive SOC pools are redistributed in the different SOC pools following the same parameters as in the CENTURY model (Guenet et al, 2016;Parton et al, 1988): 20…”
Section: Litter Soc and Doc Dynamics Within Each Soil Layermentioning
confidence: 99%
See 2 more Smart Citations